2010
DOI: 10.3917/rfs.512.0281
|View full text |Cite
|
Sign up to set email alerts
|

L'écart d'âge entre conjoints

Abstract: International audienceWarum sind die Männer durchschnittlich und praktisch in allen bekannten Gesellschaften älter als ihre Ehefrauen ? Und wie – und warum – variiert der durchschnittliche Altersunterschied zwischen Ehepartnern mit der sozioökonomischen Entwicklung (so wie im Laufe der Zeit als auch zwischen den Gesellschaften) und, innerhalb der Ehepartnern, mit dem Alter der Männer und der Frauen bei Eheschluss, sowie mit der sozialen Stellung der Männer. Zur Beantwortung dieser Frage schlagen wir ein Übersi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 40 publications
0
14
0
1
Order By: Relevance
“…Simulations illustrate that this shift will be faster if the difference between age at fatherhood and age at childbearing decreases, i.e., if age at fatherhood decreases faster than age at childbearing. The gap between male and female ages at reproduction indeed tends to narrow during the demographic transition, as does the age difference between partners (Mignot ). We may, thus, expect that decline in male fertility will take the fast track.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Simulations illustrate that this shift will be faster if the difference between age at fatherhood and age at childbearing decreases, i.e., if age at fatherhood decreases faster than age at childbearing. The gap between male and female ages at reproduction indeed tends to narrow during the demographic transition, as does the age difference between partners (Mignot ). We may, thus, expect that decline in male fertility will take the fast track.…”
Section: Discussionmentioning
confidence: 99%
“…As discussed below, these age differences at childbearing and at fatherhood are key to understanding differences between female and male fertility. They are also obviously related to differences in age at marriage between men and women: on average, men are older than their partners in virtually all countries of the world, and age differences between spouses are highest in West African countries (Mignot ).…”
Section: Differences Between Men and Women Are Often Substantialmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, relatively few families today strive for large numbers of children. These developments would seem to call into question both the economic and the reproductive part of the traditional explanation (Mignot, 2010).…”
Section: Literature Review Spousal Age Differencesmentioning
confidence: 99%
“…In heterosexual couples, husbands are on average a few years older than their wives, and men-older couples are far more common than women-older couples. This pattern appears in virtually all countries in the world and studies have shown that is has existed for a long time (Buss 1989; Casterline, Williams and McDonald 1986; Díez Minguela 2010; Gustafson and Fransson 2015; Mignot 2010). The second observation can be described as joint or synchronised retirement.…”
Section: Introductionmentioning
confidence: 97%